Affinity-Based Detection of Biomolecules Using Photo-Electrochemical Readout - Victorious, Amanda; Saha, Sudip; Pandey, Richa; Didar, Tohid F.; Soleymani, Leyla (Frontiers in Chemistry, 2019)
Detection and quantification of biologically-relevant analytes using handheld platforms are important for point-of-care diagnostics, real-time health monitoring, and treatment monitoring. Among the various signal transduction methods used in portable biosensors, photoelectrochemcial (PEC) readout has emerged as a promising approach due to its low limit-of-detection and high sensitivity. For this readout method to be applicable to analyzing native samples, performance requirements beyond sensitivity such as specificity, stability, and ease of operation are critical. These performance requirements are governed by the properties of the photoactive materials and signal transduction mechanisms that are used in PEC biosensing. In this review, we categorize PEC biosensors into five areas based on their signal transduction strategy: a) introduction of photoactive species b) generation of electron/hole donors c) use of steric hinderance d) in situ induction of light, and e) resonance energy transfer. We discuss the combination of strengths and weaknesses that these signal transduction systems and their material building blocks offer by reviewing the recent progress in this area. Developing the appropriate PEC biosensor starts with defining the application case followed by choosing the materials and signal transduction strategies that meet the application-based specifications.